2020
DOI: 10.30534/ijatcse/2020/264942020
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition from Blog Comments Based Automatically Generated Datasets and Ensemble Models

Abstract: Emotions have a large influence on product loyalty and found that an individual have a positive emotional relationship with identified product, trust in the company and make purchases. The customer's decision is not founded on their facts/ information, but they rely on their emotions to get brand loyalty decisions. However, companies are struggling to adapt this strategy even with the huge amount of data they acquired, their utilization of this data as marketing influence and ongoing personalization tactics is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Different from emotion and emotion regulation, NFA focuses on people's attitude toward emotion itself (2), and it is a psychological trait related to emotion. Although we do not find any research to date specifically on NFA identification based on network behaviors, many studies have found that users' emotions could be identified based on the blogs and blog comments they posted on social media [e.g., (33,34)].…”
Section: Introductionmentioning
confidence: 99%
“…Different from emotion and emotion regulation, NFA focuses on people's attitude toward emotion itself (2), and it is a psychological trait related to emotion. Although we do not find any research to date specifically on NFA identification based on network behaviors, many studies have found that users' emotions could be identified based on the blogs and blog comments they posted on social media [e.g., (33,34)].…”
Section: Introductionmentioning
confidence: 99%